Registros palinológicos em perfis de solos para reconstituição da vegetação no bioma Pampa - Piazza, Eliara Marin (2019)
Pampa biome vegetation is characterized by extensive areas of native grasslands interspersed by forests close to water courses. There is a great effort on the part of researchers to understand the grassland and forest dynamic so that appropriate conservation and management actions are proposed for the biome. In this sense, the present work aimed to perform a palynological record in order to reconstitute a model of past vegetation in an ecotone region in the Pampa biome. For this, four mineral soil profiles were selected in the municipality of São Gabriel, RS, Brazil. The collected soil samples were fractionated into 1cm3 and then processed according to standard methodology in palynology. The palynological analyzes were supported by radiocarbon dating and particle size analysis. The results indicated that the forestry horticulture of Cerro do Batovi was naturally composed of grassland vegetation from 4090 ± 25 years BP. The grasslands were mainly covered by grasses such as Poaceae and other herbs which inhabited open environments. In the Santa Olga forest, the grassland and forest vegetation divide space at least 2630 ± 25 years BP, however the grassland elements dominated the pollen spectrum. The particle size data indicated that the particle size of the soil exerts a direct influence on the representativeness of the pollen collection. The results will contribute to better understand the current floristic pattern of the Pampa biome, favoring development of conservation strategies. In addition, this work extends the frontier of palynological research, as well as knowledge about the potential of soil use in paleoenvironmental studies, being the first work in palynology to use mineral soils as a sampling site.